Camalexin contributes to the partial resistance of Arabidopsis thaliana to the biotrophic soilborne protist Plasmodiophora brassicae - Lemarié, Séverine; Robert-Seilaniantz, Alexandre; Lariagon, Christine; Lemoine, Jocelyne; Marnet, Nathalie; Levrel, Anne; Jubault, Mélanie; Manzanares-Dauleux, Maria J.; Gravot, Antoine (Frontiers in Plant Science, 2015)
Camalexin has been reported to play defensive functions against several pathogens in Arabidopsis. In this study, we investigated the possible role of camalexin accumulation in two Arabidopsis genotypes with different levels of basal resistance to the compatible eH strain of the clubroot agent Plasmodiophora brassicae. Camalexin biosynthesis was induced in infected roots of both Col-0 (susceptible) and Bur-0 (partially resistant) accessions during the secondary phase of infection. However the level of accumulation was four-to-seven times higher in Bur-0 than Col-0. This was associated with the enhanced transcription of a set of camalexin biosynthetic P450 genes in Bur-0: CYP71A13, CYP71A12 and CYP79B2. This induction correlated with slower P. brassicae growth in Bur-0 compared to Col-0, thus suggesting a relationship between the levels of camalexin biosynthesis and the different levels of resistance. Clubroot-triggered biosynthesis of camalexin may also participate in basal defense in Col-0, as gall symptoms and pathogen development were enhanced in the pad3 mutant (Col-0 genetic background), which is defective in camalexin biosynthesis. Clubroot and camalexin responses were then studied in Heterogeneous Inbred Families (HIF) lines derived from a cross between Bur-0 and Col-0. The Bur/Col allelic substitution in the region of the previously identified clubroot resistance QTL PbAt5.2 (Chromosome 5) was associated with both the enhanced clubroot-triggered induction of camalexin biosynthesis and the reduced P. brassicae development. Altogether, our results suggest that high levels of clubroot-triggered camalexin biosynthesis play a role in the quantitative control of partial resistance of Arabidopsis to clubroot.